Report of the Steering Group on Environment, Forests and Wastelands Development for the Formulation of the Eighth Five Year Plan (1990-95) - Planning Commission (Planning Commission, 1989)
The Sixth Five Year Plan marked the beginning of integrated and intensive efforts in conserving the natural assets. A separate chapter on Environment was introduced in the Plan document and a Department of Environment was set up at the Centre. State Governments were also requested to do likewise.
Planning Commission Government of India
Planning Commission Government of India